The Analysis of Triggering Factors for Student Disobedience With Conduct Disorder Towards School Regulations: A Case Study at SMA "MK" Yogyakarta - Annisa, Marwah; Alam, Naufal Ahmad Rijalul (ISTAWA, 2024)
Behaviour that violates school regulations by students is considered deviant. School rules are designed to create order, discipline, and a conducive learning environment. The cause of disobedience to school rules is often due to students having conduct disorder. This study analyzes the triggering factors of disobedience among SMA "MK" Yogyakarta students with conduct disorder towards school regulations. School regulations are an important part of discipline that must be followed by students. This research aims to identify the factors that trigger rule violations in the school environment committed by students with conduct disorders. This research uses a descriptive qualitative method with in-depth interviews with six high school students from grades X to XII as research subjects. The results show that student disobedience is influenced by internal factors, such as uncontrolled emotions, the need for recognition, and the search for identity, as well as external factors, such as the negative influence of the family environment, peers, and the school environment. The implementation of inflexible rules and monotonous teaching methods also contributes to violations. This research recommends a holistic approach involving support from families, schools, and counseling interventions to address this issue.